The Gateway to Computer Science Excellence
0 votes
Using Armstrong’s axioms of functional dependency derive the following rules:

$\{ x \rightarrow y, \: x \rightarrow z \} \mid= x \rightarrow yz$

(Note: $x \rightarrow y$ denotes $y$ is functionally dependent on $x$, $z \subseteq y$ denotes $z$ is subset of $y$, and $\mid =$ means derives).
in Databases by Veteran (105k points) | 142 views

1 Answer

+2 votes
Best answer
$x \rightarrow z$  (Given)

$\implies xx \rightarrow zx$ (Axiom of augmentation)  $\qquad \to(I)$

Also $x \rightarrow y$ (Given)

$\implies xz \rightarrow yz$ (Axiom of augmentation) $\qquad \to (II)$

Using $(I)$ and $(II)$ we get

$xx \rightarrow yz$ (Axiom of transitivity)

$\implies x \rightarrow yz$
by Boss (21.7k points)
selected by

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,645 questions
56,596 answers
102,082 users